Mannich base metal complexes and their thiocyanate analogues as catalysts in the oxidation of Catechol - Ayeni, Ayowole Olaolu (Rhodes University, Faculty of Science, Department of Chemistry, 2018)
The study focused on the design of new Cu(II) and Fe(III) complexes, with or without thiocyanate (NCS-), as possible candidates of catechol oxidation using 3,5-di-tert-butyl catechol (3,5-DTBC) as substrate. Two classes of Mannich bases were studied depending on the active methylene group from which they were formed, being either p-cresol or acetaminophen. The ligands were characterised by 1H and 13C NMR spectroscopy. Crystal structures of three of the ligands are newly reported, along with detailed discussion of polymorphism observed in one of the ligands, and the nature of the hydrogen within the ligands in the solid state as well as in solution. The Mannich bases behaved as bidentate (NO), tridentate (NNO) and tetradentate (NNOO) ligands on coordination to Cu(II) and Fe(III) ions in which the hydroxyl group may be protonated or deprotonated. Coordination was determined by IR spectroscopy, investigating shifts in vOH, vC-O and in vCNC of the Mannich bases. The vCNC stretching frequencies v1 and v2 of asymmetrical piperazine Mannich bases were observed to shift upward in few cases upon complexation and this is attributed to (chair-boat) conformational change. The mode of coordination of the thiocyanate was determined by IR spectroscopy. Of the forty metal complexes investigated, six groups of metal complexes were identified as follows: (i) Ma(Ln)aClb-cH2O; (ii) Ma(HLn)a(NCS)aClb; (iii) Ma(Ln)a(NCS)aClb; (iv) Ma(HLn)aClb-cH2O; (v) Ma(Ln)a(NCS)a-cH2O; (vi) Ma(HLn)a(NCS)a-cH2O where a = 1 - 2 ; b = 1 - 4, c = 1 - 8. Molar conductivity values of 4.38 - 161.77 Q-1.cm2.mol-1 for the Cu(II) and Fe(III) complexes in DMSO showed that they range from non-electrolytes to 1:1 and 1:2 electrolytes. Electronic spectra for the ligands and the complexes were conducted in DMF and DMSO. The ligands are characterised by and n→n* and n→n* transitions. Intraligand charge transfer transitions peculiar to the nitro group were observed at about 430 nm for the nitro containing ligands. On coordination, these bands overshadowed the d-d transitions particularly for the nitro-Mannich bases. On complexation, ligand to metal charge transfer transitions associated with the hydroxyl were observed between 320 - 420 nm. Charge transfer transitions associated with the thiocyanates were also observed and discussed. The d-d transitions for high spin Fe(III) complexes are spin forbidden and generally uninformative. Those of Cu(II) are spin allowed and allow tentative structural proposals. Square planar and octahedral geometry are generally prevalent in the Cu(II) complexes with trigonal bipyramidal observed in few instances. The Fe(III) complexes are generally octahedral. Thirty-nine of the forty synthesised Cu(II) and Fe(III) complexes were catalytically active on the substrate (3,5-DTBC) in DMF with turnover rates (kcat) reported in the range of 1.86 ± 0.09 to 112.32 ± 3.72 h-1. From this pool of complexes, sixteen isostructural pairs were identified in terms of geometry, molecular formula and the source of the Mannich base and the following conclusions were made: The presence of thiocyanate in the metal complexes reduce catecholase activity; the Cu(II) complexes generally have better activity but the Fe(III) complexes become more relatively active with highly electron donating groups while the Cu(II) complexes become less; dinuclear complexes have greater activity than the mononuclear.
Keywords: Mannich bases; Catechol; Catechol -- Oxidation; Thiocyanates; Catalysts